A protocol combining multiphoton microscopy and propidium iodide for deep 3D root meristem imaging in rice: application for the screening and identification of tissue-specific enhancer trap lines - Charlotte Bureau; Nadège Lanau; Mathieu Ingouff; Boukhaddaoui Hassan; Anne-Cécile Meunier; Fanchon Divol; Rosie Sevilla; Delphine Mieulet; Anne Dievart; Christophe Périn (Plant Methods, 2018)
Abstract Background The clear visualization of 3D organization at the cellular level in plant tissues is needed to fully understand plant development processes. Imaging tools allow the visualization of the main fluorophores and in vivo growth monitoring. Confocal microscopy coupled with the use of propidium iodide (PI) counter-staining is one of the most popular tools used to characterize the structure of root meristems in A. thaliana. However, such an approach is relatively ineffective in species with more complex and thicker root systems. Results We adapted a PI counter-staining protocol to visualize the internal 3D architecture of rice root meristems using multiphoton microscopy. This protocol is simple and compatible with the main fluorophores (CFP, GFP and mCherry). The efficiency and applicability of this protocol were demonstrated by screening a population of 57 enhancer trap lines. We successfully characterized GFP expression in all of the lines and identified 5 lines with tissue-specific expression. Conclusions All of these resources are now available for the rice community and represent critical tools for future studies of root development.